Accounting for racial wealth disparities in the United States - Thompson, Jeffrey P.,Suárez, Gustavo A. (Federal Reserve Bank of Boston, 2019)
Using data from the Survey of Consumer Finances, this paper updates and extends previous research on the racial wealth gap in the United States. We explore several hypotheses that help explain differential wealth accumulation by racial groups, including the importance of receiving inheritances and other financial support from relatives and the conditions in local real estate markets. By exploring the disparities among white, black, and Hispanic families, we make new contributions to the literature. We find that observable factors account for the entire wealth gap between white and Hispanic families and most of the gap between white and black families. Differences in human capital, demographics, and family financial support each make substantial contributions to the wealth gaps we observe between white and nonwhite families. Yet a substantial portion of the wealth gap between white and black families remains unaccounted for after a detailed decomposition. This unexplained portion is greater at the top of the wealth distribution.
10419/227928
Keywords: Graue Literatur; racial wealth gap; inequality; inheritance; savings